Jurnal Skripsi ANALISIS PEMAHAMAN MAKNA KONOTATIF DAN DENOTATIF PADA LIRIK LAGU DAUR HIDUP KARYA DONNE MAULA: Pemahaman makna konotatif dan denotatif padea liriiki lagu daur hidup kiarya Donne Maula - Jesicca Winada Br Sembiring; Alfitriana Purba (Universitas Asahan, 2025)
Language in song lyrics conveys not only literal meanings (denotative) but also emotional and symbolic nuances (connotative). The song “Daur Hidup” by Donne Maula is a musical composition rich in expressive diction, reflecting the complexities of life through layered meanings. This study aims to identify and describe the denotative and connotative meanings embedded in the lyrics of the song using a semantic approach. Employing a qualitative method with a descriptive design, data were collected through attentive listening and note-taking techniques, followed by semantic analysis. The findings reveal that each line of the lyrics contains denotative meanings that represent literal interpretations, as well as connotative meanings that express emotional states, life struggles, and symbolic references. Phrases such as “ditempa” (forged), “mati berkali-kali tapi bisa hidup lagi” (die many times but still live again), and “bohong jika aku bilang selalu kuat” (it’s a lie if I say I’m always strong) exemplify the emotional depth and existential themes conveyed through the lyrics. This study demonstrates that semantic analysis is effective in uncovering hidden meanings within lyrical texts and underscores the role of song lyrics as a form of artistic and reflective expression.